2020
DOI: 10.1101/2020.11.30.402917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

YeastNet: Deep Learning Enabled Accurate Segmentation of Budding Yeast Cells in Bright-field Microscopy

Abstract: Accurate and efficient segmentation of live-cell images is critical in maximising data extraction and knowledge generation from high-throughput biology experiments. Despite recent development of deep learning tools for biomedical imaging applications, great demand for automated segmentation tools for high-resolution live-cell microscopy images remains in order to accelerate the analysis. YeastNet dramatically improves the performance of non-trainable classic algorithm, and performs considerably better than the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Among the different imaging modalities, brightfield illumination with transmitted light is the simplest to acquire while avoiding damaging the sample 1 . The usefulness of this technology has led to its widespread adoption 24 , and thereby to a dramatic increase in the volumes of microscopy data. However, the automated analysis techniques required to extract information at scale are often hindered by the artifacts present in the images 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the different imaging modalities, brightfield illumination with transmitted light is the simplest to acquire while avoiding damaging the sample 1 . The usefulness of this technology has led to its widespread adoption 24 , and thereby to a dramatic increase in the volumes of microscopy data. However, the automated analysis techniques required to extract information at scale are often hindered by the artifacts present in the images 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the U-Net architecture and its variants such as Unet++ (Zhou et al, 2018), 3D Unet (Çiçek et al, 2016), and V-Net (Milletari et al, 2016) can obtain high segmentation accuracy. Motivated by the good performance of U-Nets in cell segmentation (Van Valen et al, 2016;Hollandi et al, 2020;Salem et al, 2020), we developed Dice-XMBD, a deep neural network (DNN)-based cell segmentation method for multichannel IMC images. Dice-XMBD is marker agnostic and can perform cell segmentation for IMC images of different channel configurations without modification.…”
Section: Introductionmentioning
confidence: 99%
“…Although many software tools dedicated to the analysis of budding yeast live-cell microscopy have been developed in the past (ImageJ/Fiji 10 , MorphoLibJ 11 , PhyloCell 12 , CellProfiler 13 , Cell Tracer 14 , Wood et al 15,16 , Cell Star 17 , Cell Serpent 18 , CellID 19 , Tracker 20 , DISCO 21 , YeastSpotter 22 , YeastNet 23 , DeepCell 24 , Cellbow 25 ), to the best of our knowledge, none of them spanned the entire image analysis pipeline from CNN-base segmentation to cell cycle analysis, and fluorescent signal quantification.…”
Section: Introductionmentioning
confidence: 99%